GIAO-DFT calculated and experimentally derived complexation-induced chemical shifts of calix[4]arene-solvent inclusion complexes - Schatz, Jürgen; et al. (Journal of the Chemical Society, Perkin Transactions 2, 2002)
Various possible geometries of host-guest complexes of p-tert-butylcalix[4]arene with guest molecules such as toluene or THF are modeled using fast force field optimisations. Based on minima structures obtained by this approach quantum chemical gauge-independent atomic orbital (GIAO)-DFT NMR calculations [B3LYP/3-21G and B3LYP/6-31G(d)] were performed. By a comparison of the theoretically derived chemical shifts for the guest molecule in the host-guest complex with the chemical shifts calculated for the free guest using the same theoretical approach, calculation of complexation-induced chemical shifts (CISs) is possible. Spatial arrangements for which the theoretically derived complexation-induced shifts are in accordance with data stemming from CP-MAS C NMR spectroscopy also show reasonable agreement with structures obtained by single crystal structure determinations. Thus, it is possible for calix[4]arene complexes using a combination of force field geometry optimisation and GIAO-DFT NMR shift calculations to screen various starting geometries against experimental data yielding good structural models for these complexes in the solid state.